2006
DOI: 10.1007/s00432-006-0092-x
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of short-chain fatty acids on colon epithelial proliferation and survival depend on the cellular phenotype

Abstract: Although butyrate could exert antiproliferative effects in tumor progression, its production is safe and without consequences for the normal epithelium growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 50 publications
6
127
0
9
Order By: Relevance
“…As this SCFA did not induce apoptosis at the concentrations used in this study, we conclude that butyrate inhibits epithelial proliferation. Several in vitro studies support our finding that butyrate inhibits proliferation [33][34][35][36][37]. For example, butyrate inhibited the proliferation of non-confluent and sub-confluent HT-29 cells in a dosedependent manner (1-8 mM) [36].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As this SCFA did not induce apoptosis at the concentrations used in this study, we conclude that butyrate inhibits epithelial proliferation. Several in vitro studies support our finding that butyrate inhibits proliferation [33][34][35][36][37]. For example, butyrate inhibited the proliferation of non-confluent and sub-confluent HT-29 cells in a dosedependent manner (1-8 mM) [36].…”
Section: Discussionsupporting
confidence: 81%
“…Several in vitro studies support our finding that butyrate inhibits proliferation [33][34][35][36][37]. For example, butyrate inhibited the proliferation of non-confluent and sub-confluent HT-29 cells in a dosedependent manner (1-8 mM) [36]. Furthermore, Siavoshian et al demonstrated that the mechanism through which butyrate inhibits proliferation in HT-29 cells is exerted via the induction of cyclin D3, an inhibitor of cell cycle progression and p21, a stimulator of cell differentiation [33].…”
Section: Discussionsupporting
confidence: 80%
“…Butyrate, a histone deacetylase inhibitor that evokes pronounced transcriptional changes in different types of cultured epithelial cell lines (22)(23)(24)(25), is the preferred energy substrate for colonic enterocytes (26). While transcriptional changes caused by butyrate differ depending upon the cell lineage, state of cellular differentiation, and cellular energy status (23,24,27,28), in vitro and in vivo studies have shown that it affects expression of genes involved in proliferation, differentiation and apoptosis (25,28).…”
Section: Colonic Transcriptional Changes Evoked By E Rectale-b Thetmentioning
confidence: 99%
“…Comalada et al (72) compared the effects of butyrate treatment on healthy fetal human colon cells and on HT-29 colorectal adenocarcinoma cells. Butyrate inhibited cell proliferation of the HT-29 cells but had no effect on the normal cells.…”
Section: The Effects Of Resistant Starch and Butyrate On Colonic Crypmentioning
confidence: 99%